PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KREATIVITAS MELALUI MOTIVASI INTRINSIK(STUDI PADA KARYAWAN DIVISI PRODUKSI PT.DOK DAN PERKAPALAN SURABAYA PERSERO) - CITRA WULANSARI, RHISANTIKA (Jurnal Ilmu Manajemen (JIM), 2016)
Peran seorang pemimpin transformasional menjadi faktor terpenting dalam menghadapi persaingan dunia industriuntuk dapat mempengaruhi para karyawan mereka sehingga motivasi intrinsik karyawan meningkat dan berpengaruh terhadap peningkatan kreativitas karyawan.Tujuan dari penelitian ini adalah untuk menguji pengaruh gaya kepemimpinan transformasional terhadap kreativitas melalui motivasi intrinsik (Studi Pada Karyawan Divisi Produksi PT.DOK Dan Perkapalan Surabaya Persero). Jenis penelitian ini adalah penelitian ini adalah penelitian kausalitas, dengan pendekatan kuantitatif. Penelitian ini menggunakan teknik simple random samplingdan di analisis menggunakan metode structural equation modeling (SEM).Penelitian ini menggunakan sampel sebanyak 123 responden yang diambil dari karyawan PT. DOK dan Perkapalan Surabaya (Persero) di Departemen Produksi. Skala pengukuran dalam penelitian ini menggunakan skala likert. Hasil penelitian menunjukkan bahwa terdapat pengaruh langsung yang signifikan pada kepemimpinan transformasional terhadap motivasi intrinsik. Terdapat pengaruh langsung yang signifikan dari variabel motivasi intrinsik terhadap kreativitas. The role of a transformational leader is the most important factor in the face of world competition may affect the industry for their employees so that the intrinsic motivation of employees to rise and affect the development of the creativity of employees. The purpose of this study was to examine the effect of transformational leadership style towards creativity through intrinsic motivation (A Case Study Of Employees And Division Production PT. DOK Dan Perkapalan Surabaya). This type of research was causality, with a quantitative approach. This study using simple random sampling technique and analyzed using StructuralEquation Modeling (SEM) analysis method. This study used a sample of 123 respondents drawn from employees of PT. DOK Dan Perkapalan Surabaya in the Production Department. The scale of measurement in this study using a Likert scale. The results showed that there was a significant direct effect on transformational leadership on intrinsic motivation. There was a significant direct effect of variable intrinsic motivation to creativity. But there was no direct influence of variables transformational leadership on creativity. The role of a transformational leader is the most important factor in the face of world competition may affect the industry for their employees so that the intrinsic motivation of employees to rise and affect the development of the creativity of employees. The purpose of this study was to examine the effect of transformational leadership style towards creativity through intrinsic motivation (A Case Study Of Employees And Division Production PT. DOK Dan Perkapalan Surabaya). This type of research was causality, with a quantitative approach. This study using simple random sampling technique and analyzed using StructuralEquation Modeling (SEM) analysis method. This study used a sample of 123 respondents drawn from employees of PT. DOK Dan Perkapalan Surabaya in the Production Department. The scale of measurement in this study using a Likert scale. The results showed that there was a significant direct effect on transformational leadership on intrinsic motivation. There was a significant direct effect of variable intrinsic motivation to creativity. But there was no direct influence of variables transformational leadership on creativity.